The building stone of the Roman city of Lixus (NW Morocco): provenance, petrography and petrophysical characterization - T. Ajanaf; D. Gómez-Gras; A. Navarro; J.D. Martín-Martín; J.R. Rosell; A. Maate (Geologica Acta, 2020)
The characterization of building materials is a key tool to assess deterioration processes and improve potential restoration works of archaeological sites. The aim of this paper is to identify and characterize the most important building stones used in the construction of the Roman city of Lixus (Larache, Morocco) by means of petrographic and petrophysical techniques. Based on the visual analysis of the monuments, three major building stones (i.e. lithotypes) have been identified: i) Oligocene sandstones, ii) Quaternary sandstones and iii) Quaternary conglomerates. Based on the analysis of the regional geology and exploitation marks, these three lithotypes have been recognised to crop out in the surroundings of Lixus and the quarries, presumably Roman in origin, recognized. The Oligocene sandstone is the primary building stone in Lixus as it forms and crops out extensively in the Tchemmis hill, at the top of which the city is settled. The Quaternary sandstones and conglomerates, which represent nearshore deposits and eolianites, crop out along the Atlantic coast where they form part of the cliffs next to Larache. Petrographic results indicate that lithotypes differ notably in grain size, ratio of detrital to allochemical components, and the configuration of their porous system. Mechanical analysis shows that the Oligocene sandstones are more resistant to compression than the Quaternary sandstones and conglomerates, the latter exhibiting relatively low compressive strength. The Oligocene sandstones, which display scarce porosity and permeability, show a hydric behaviour characterized by a very low degree of absorption and desorption water, likely resulting from a poor connectivity of the pore network. Contrary to the latter lithotype, the Quaternary sandstones, which exhibit very high porosity and permeability, display a hydric behaviour characterized by high degree of both absorption and desorption of water. This is attributed to the low degree of cementation compared to porosity of this lithotype and the excellent connectivity of the porous network. Finally, Oligocene and Quaternary sandstones do not show a significant weight loss after the accelerated artificial aging test, indicating that both are slightly affected by salt crystallization and presumably ice formation. Results indicate that the relatively fine state of conservation of the building rocks of Lixus is linked to intrinsic factors such as mineralogy and petrophysical characteristics together with the favourable effect of the climatic condition of the study area.